PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE PADA MATERI KENAMPAKAN ALAM MATA PELAJARAN IPS, KELAS IV SD NEGERI 1 ULU SEMONG - Yunaya; Haris Agus Istanto; Suwanto (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2023)
Based on the existing formative results, student learning outcomes on natural appearance material are low, because the completeness of learning outcomes only reaches 30% of the 19 fourth grade students. The results of reflection and discussion with colleagues and supervisors, it is necessary to have learning that is focused on the visualization of learning material. Therefore, it is necessary to make efforts to improve student learning outcomes through the implementation of Classroom Action Research in class IV SD Negeri 1 Ulu Semong with 2 cycles and one of the actions taken is to use the picture and picture learning model. Data was collected through instrument tests for learning outcomes and observation sheets to observe learning activities which were then analyzed by reducing and classifying data. At the stage of implementing more active actions it is shown, student learning activities are tinkering with the images presented. Besides that, students are also more enthusiastic about asking about the pictures given, which indicates increasing student curiosity. At the end of the second cycle, the data showed that the students' mastery had increased from 32% in the pre-cycle to 89% in the second cycle. Thus it can be interpreted that student learning outcomes of natural appearance can be improved by using picture and picture learning models.